The Development of Anyflip Media Based on The PjBL Model on PPKN Subjects at SMK Muhammadiyah 1 Kemlagi, Mojokerto Regency - Mustaji; Maksum Efendy Firdaus; I Wayan Arsana (Jurnal Mantik, 2022)
This study aims to produce Anyflip Media Based on the PjBL Model on appropriate PPKN subjects. The development model used is Dick & Carey. The development process involves subject matter experts, instructional design experts and learning media experts to provide feedback and suggestions for improvement. In addition, teachers of PPKN subjects and students of SMK Muhammadiyah 1 Kemlagi Mojokerto Regency as users of the Pjbl Model-Based Anyflip Media also gave their feedback and input. The results of this development research are (1) The Development of Anyflip Media Based on the Pjbl Model in Civics Subjects developed based on the needs analysis of teachers and students through a needs questionnaire provided by the developer, (2) The results of the validation of material experts, media experts, and design experts on product development Anyflip Media Based on the Pjbl Model in Civics Subjects with very feasible criteria to be developed, and (3) Based on the results of research on the development of the Pjbl Model-Based Anyflip Media in PPKN Subjects, it can be concluded that the Anyflip Media Based on the Pjbl Model is used in developing abilities in designing creative learning , innovative and interesting. Based on the results of this study, it was concluded that using Anyflip Media Based on the Pjbl Model could improve student learning outcomes in PPKN at SMK Muhammadiyah 1 Kemlagi, Mojokerto Regency. The implication of this research is that Anyflip Media Based on the Pjbl Model can be used as a way to improve student learning outcomes for PPKN.